PERILAKU MENGGANGGU DI KELAS - Taufiq Hendra Wicaksono (Paradigma, 2012)
Characteristics and indicators of disruptive behavior andthere is no common characteristic at each age level school(playgroup, kindergarten, elementary, junior high, high school oruniversity). Disruptive behavior can be divided into three levels,namely mild, moderate and severe. The reasons for this can comefrom internal or external actors. Handling problems and disruptivebehavior can be observed from behavioristik approaches, cognitiveand humanistic. Through this article classroom teachers and teacherguidance and counseling are expected to understand and handledisruptive behavior so as to maximize the teaching and learningprocess in the classroom.Key words : Disruptive Behavior, teacher guidance and counseling,learning process